Preliminary Perception of Veterinarians from Northwestern Argentina Regarding the Teaching of Veterinary Pathology and Its Usefulness in Professional Practice (FAVE Sección Ciencias Veterinarias, 2025)
Veterinary pathology is essential for clinical practice, especially in regions such as Northwestern Argentina (NOA), where diagnostic resources are scarce and most veterinary work is done in rural areas. To explore professional perceptions of training in this field, a survey was administered to 54 veterinarians from NOA. Although 64.8% of the veterinarians considered their pathology training useful, only 44.5% felt that it was clearly oriented toward practical application. Necropsy was highly valued, yet professionals reported limitations, including a lack of equipment and training and logistical challenges. The use of histopathology was low, mainly due to limited access to fixatives, issues with transporting samples, and delayed results. Respondents expressed strong interest in receiving more hands-on training, particularly in necropsy techniques and sample selection. These findings highlight a persistent gap between academic training and professional practice realities. Strengthening practical teaching, promoting active methodologies such as clinical case analysis, and aligning veterinary education with local contexts are recommended to enhance diagnostic capacity in resource-constrained areas.
Keywords: veterinary pathology; necropsy; histopathology; veterinary education; Northwestern Argentina